Matrix metalloproteinases and their natural inhibitors in fibrovascular membranes of proliferative diabetic retinopathy. Issue 10 (1st October 2000) - Salzmann, Joel; Limb, G Astrid; Khaw, Peng T; Gregor, Zdenek J; Webster, Lynne; Chignell, Anthony H; Charteris, David G
Abstract : AIM: To examine epiretinal membranes of proliferative diabetic retinopathy (PDR) for the presence of selective matrix metalloproteinases (MMPs) and their natural inhibitors (TIMPs), in order to determine whether neovascularisation and fibrosis, characteristic of this complication of diabetes mellitus, are associated with specific anomalies of MMP or TIMP expression. METHODS: The presence of selected MMPs and TIMPs was investigated in 24 fibrovascular epiretinal membranes of PDR, and the findings compared with that observed in 21 avascular epiretinal membranes of proliferative vitreoretinopathy (PVR) and five normal retinas. Specimens were examined for deposition of interstitial collagenase (MMP-1), stromelysin-1 (MMP-3), gelatinase A (MMP-2), gelatinase B (MMP-9), and three tissue inhibitors of metalloproteinases (TIMP-1, TIMP-2, and TIMP-3). RESULTS: The results showed that unlike normal retina, which constitutively expresses MMP-1 and TIMP-2, a large proportion of PDR membranes (> 62%) stained for MMP-1, MMP-2, MMP-3, MMP-9, TIMP-1, TIMP-2, and TIMP-3. There were no differences in the expression of these molecules when compared with PVR membranes. A characteristic staining for MMP-9 was observed within the perivascular matrix of PDR membranes, and there was a significant increase in TIMP-2 expression by PDR membranes (p= 0.036) when compared with PVR membranes. CONCLUSIONS: The findings that MMPs involved in degradation of fibrovascular tissue matrix, as well as TIMP-1 and TIMP-2, are found in a large proportion of PDR membranes, and that their expression does not differ from that of PVR membranes, suggest the existence of common pathways of extracellular matrix degradation in pathological processes leading to retinal neovascularisation and fibrosis.